Limited partner performance and the maturing of the private equity industry - Sensoy, Berk A.; Wang, Yingdi; Weisbach, Michael S. (Journal of Financial Economics, 2014)
We evaluate the performance of limited partners׳ (LPs׳) private equity investments over time. Using a sample of 14,380 investments by 1,852 LPs in 1,250 buyout and venture capital funds started between 1991 and 2006, we find that the superior performance of endowment investors in the 1991–1998 period, documented by prior literature, is mostly due to their greater access to the top-performing venture capital partnerships. In the subsequent 1999–2006 period, endowments no longer outperform, no longer have greater access to funds that are likely to restrict access, and do not make better investment selections than other types of institutional investors. Nevertheless, all investor types׳ private equity investments continue to outperform public markets on average. We discuss how these results are consistent with the general maturing of the industry, as private equity has transitioned from a niche, poorly understood area to a ubiquitous part of institutional investors׳ portfolios.